Differential Uplift of the Eastward Mountain Front of Olympus Mt (Greece) based on Tectonic Geomorphology Observations - Sakellaropoulos, P.; Vassilakis, Emm.; Tranos, M.; Lozios, S. (Reg. Conf. on Geomorphology (IAG), 2019)
The study of the east dipping N-S mountain front of Olympus Mt that is presented in this work, was based on the interpretation of high-resolution digital elevation model (DEM), as the main dataset for calculating various tectonic geomorphology indices, through quantitative techniques. Since the fluvial network maintains its connection to the tectonic forcing and therefore contains potentially useful information about variations in rock uplift rates across the landscape, we used a highly detailed one generated from the DEM in order to calculate various indices and extract quantitate information. Calculations were made in a GIS platform by using the Ks index, the drainage basin asymmetry index and the geometry of the triangular facets on the front of the mountain, alongside the fault zone delineating the mountain. The results extracted by combining the previous methodologies are in agreement with the observations which were made during the fieldwork, that there is no uniform uplift along the main Olympus fault zone.